Cannabigerol–A useful agent restoring the muscular phospholipids milieu in obese and insulin-resistant Wistar rats? - Bielawiec, Patrycja; Dziemitko, Sylwia; Konstantynowicz-Nowicka, Karolina; Sztolsztener, Klaudia; Chabowski, Adrian; Harasim-Symbor, Ewa (Frontiers in Molecular Biosciences, 2024)
Numerous strategies have been proposed to minimize obesity-associated health effects, among which phytocannabinoids appear to be effective and safe compounds. In particular, cannabigerol (CBG) emerges as a potent modulator of the composition of membrane phospholipids (PLs), which plays a critical role in the development of insulin resistance. Therefore, here we consider the role of CBG treatment on the composition of PLs fraction with particular emphasis on phospholipid subclasses (e.g., phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS), and phosphatidylinositol (PI)) in the red gastrocnemius muscle of Wistar rats fed the standard or high-fat, high-sucrose (HFHS) diet. The intramuscular PLs content was determined by gas-liquid chromatography and based on the composition of individual FAs, we assessed the stearoyl-CoA desaturase 1 (SCD1) index as well as the activity of n-3 and n-6 polyunsaturated fatty acids (PUFAs) pathways. Expression of various proteins engaged in the inflammatory pathway, FAs elongation, and desaturation processes was measured using Western blotting. Our research has demonstrated the important association of obesity with alterations in the composition of muscular PLs, which was significantly improved by CBG supplementation, enriching the lipid pools in n-3 PUFAs and decreasing the content of arachidonic acid (AA), which in turn influenced the activity of PUFAs pathways in various PLs subclasses. CBG also inhibited the local inflammation development and profoundly reduced the SCD1 activity. Collectively, restoring the PLs homeostasis of the myocyte membrane by CBG indicates its new potential medical application in the treatment of obesity-related metabolic disorders.